The unmet need for pertussis prevention in patients with chronic obstructive pulmonary disease in the Italian context. Issue 2 (1st February 2020) - Blasi, Francesco; Bonanni, Paolo; Braido, Fulvio; Gabutti, Giovanni; Marchetti, Federico; Centanni, Stefano
ABSTRACT: Despite high rates of vaccination, pertussis resurgence has been reported worldwide in recent years, including in Italy, especially in older adults. Chronic obstructive pulmonary disease (COPD) is a respiratory disease associated with progressive inflammation of the respiratory tract. Regional population studies have shown the prevalence of COPD in Italy to be approximately 15% with an age-dependent increase in proportion of COPD cases. Emerging data shows that individuals with COPD are at high risk of contracting pertussis. Furthermore, those who develop pertussis could experience exacerbation of their pre-existent COPD and further susceptibility to other infections. Immunization programs in Italy currently recommend a decennial reduced-antigen-content diphtheria-tetanus-acellular pertussis booster vaccine dose for adults. Active measures to encourage booster vaccination, especially for high-risk adults such as those with COPD, could positively impact pertussis morbidity and the associated healthcare burden.